(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
In the article are discussed the problems of productive using of nature-recourse potential of one of necessary factors for ecologyzation of agriculture of RA. It will be possible with optimization of recourse cycle of soil, climatic and agricultural raw material. This strategy promotes to regulation of nature using, nature protection and also to increasing of productivity of using of nature-recourse potential.